Experiment and modeling of submarine emergency rising motion using free-running model - Jooho Lee; Seonhong Kim; Jihwan Shin; Jaemoon Yoon; Jinheong Ahn; Minjae Kim (International Journal of Naval Architecture and Ocean Engineering)
Development of submarine and its safe operational envelope requires an understanding of motion characteristics including emergency rising motion. In this study, the emergency rising motion is investigated using submarine free-running model equipped with ballast systems. The emergency rising test was conducted according to the initial vehicle speed, yaw rate, depth, ballast water discharge ratio and time interval between bow and stern ballast systems. Experimental results reveal that the maximum pitch angle before surface is affected by initial velocity and the operation conditions of ballast systems. In addition, excessive roll occurs after the surface when the submarine passes through the water surface at a negative pitch angle. Furthermore, the system parameters that comprise the emergency rising model are estimated using the collected test data. The identified model is verified by comparing emergency rising simulation with the free-running model test results.